2008
DOI: 10.1016/j.jmoneco.2008.05.009
|View full text |Cite
|
Sign up to set email alerts
|

The brevity and violence of contractions and expansions

Abstract: Early studies of business cycles argued that contractions in economic activity were briefer (shorter) and more violent (rapid) than expansions. This paper systematically investigates this claim and in the process discovers a robust new business cycle fact: contractions in employment are briefer and more violent than expansions but we cannot reject the null of equal brevity and violence for expansions and contractions in output.The di¤erence arises because employment typically lags output around peaks but they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 55 publications
(34 reference statements)
2
29
0
Order By: Relevance
“…The original algorithm considers a minimum phase-length criterion of 5 months and cycle-length criterion of 15 months, but the amplitude of expansions and recessions is not taken into account. However, other works (Artis et al 1997;Mönch and Uhlg 2005;McKay and Reis 2008) have included additional restrictions in accordance with the specific features of the data that can differ from the established by the NBER for US. So, taking into account the characteristics of our data, we have incorporated a minimum amplitude criterion that excludes phases (peak to trough or trough to peaks) that have an amplitude of less than one standard deviation of the corresponding growth rates (negative or positive) in the series to be dated.…”
Section: Cycle Dating and Basic Featuresmentioning
confidence: 99%
“…The original algorithm considers a minimum phase-length criterion of 5 months and cycle-length criterion of 15 months, but the amplitude of expansions and recessions is not taken into account. However, other works (Artis et al 1997;Mönch and Uhlg 2005;McKay and Reis 2008) have included additional restrictions in accordance with the specific features of the data that can differ from the established by the NBER for US. So, taking into account the characteristics of our data, we have incorporated a minimum amplitude criterion that excludes phases (peak to trough or trough to peaks) that have an amplitude of less than one standard deviation of the corresponding growth rates (negative or positive) in the series to be dated.…”
Section: Cycle Dating and Basic Featuresmentioning
confidence: 99%
“…However, to compare the relative magnitude of di¤erent recessions over a period that displays major changes in the volatility of the business cycle, it is appropriate to control for the average variability of the cycle around a given recessionary episode. To this end, the second column of For earlier analyses on the violence and brevity of economic contractions see Mitchell (1927) and, more recently, McKay and Reis (2008). 8 The volatility is calculated as the standard deviation of the year-on-year growth rate of real GDP over a 5-year window.…”
Section: [Insert Figure 3]mentioning
confidence: 99%
“…GDP time series do not display any clear asymmetry in increases and decreases of GDP (but changes in GDP are a poor indicator of structures being lost or generated). The generation of jobs is generally slower than their destruction [122], but the difference is too small to talk of separation of time scales. Gabaix [123] showed that many macroeconomic fluctuations result from fluctuations in large firms, but these include both increases and decreases in activity, with no apparent asymmetry; moreover, none of the examples that he examined in more detail involved the failure of the firm causing the fluctuation.…”
Section: Self-organized Criticalitymentioning
confidence: 99%